A wheat transcription factor positively sets seed vigour by regulating the grain nitrate signal. Issue 4 (13th November 2019) - Li, Wenjing; He, Xue; Chen, Yi; Jing, Yanfu; Shen, Chuncai; Yang, Junbo; Teng, Wan; Zhao, Xueqiang; Hu, Weijuan; Hu, Mengyun; Li, Hui; Miller, Anthony J.; et al.
Summary: Seed vigour and early establishment are important factors determining the yield of crops. A wheat nitrate‐inducible NAC transcription factor, TaNAC2, plays a critical role in promoting crop growth and nitrogen use efficiency (NUE), and now its role in seed vigour is revealed. A TaNAC2 regulated gene was identified that is a NRT2‐type nitrate transporter TaNRT2.5 with a key role in seed vigour. Overexpressing TaNAC2‐5A increases grain nitrate concentration and seed vigour by directly binding to the promoter of TaNRT2.5‐3B and positively regulating its expression. TaNRT2.5 is expressed in developing grain, particularly the embryo and husk. In Xenopus oocyte assays TaNRT2.5 requires a partner protein TaNAR2.1 to give nitrate transport activity, and the transporter locates to the tonoplast in a tobacco leaf transient expression system. Furthermore, in the root TaNRT2.5 and TaNRT2.1 function in post‐anthesis acquisition of soil nitrate. Overexpression of TaNRT2.5‐3B increases seed vigour, grain nitrate concentration and yield, whereas RNA interference of TaNRT2.5 has the opposite effects . The TaNAC2‐NRT2.5 module has a key role in regulating grain nitrate accumulation and seed vigour. Both genes can potentially be used to improve grain yield and NUE in wheat.